Assessing health centre systems for guiding improvement in diabetes care - Robinson Gary; Stewart Allison; Dowden Michelle; Connors Christine; Bailie Ross; Si Damin; Cunningham Joan; Weeramanthri Tarun (BMC, 2005)
Abstract Background Aboriginal people in Australia experience the highest prevalence of diabetes in the country, an excess of preventable complications and early death. There is increasing evidence demonstrating the importance of healthcare systems for improvement of chronic illness care. The aims of this study were to assess the status of systems for chronic illness care in Aboriginal community health centres, and to explore whether more developed systems were associated with better quality of diabetes care. Methods This cross-sectional study was conducted in 12 Aboriginal community health centres in the Northern Territory of Australia. Assessment of Chronic Illness Care scale was adapted to measure system development in health centres, and administered by interview with health centre staff and managers. Based on a random sample of 295 clinical records from attending clients with diagnosed type 2 diabetes, processes of diabetes care were measured by rating of health service delivery against best-practice guidelines. Intermediate outcomes included the control of HbA1c, blood pressure, and total cholesterol. Results Health centre systems were in the low to mid-range of development and had distinct areas of strength and weakness. Four of the six system components were independently associated with quality of diabetes care: an increase of 1 unit of score for organisational influence, community linkages, and clinical information systems, respectively, was associated with 4.3%, 3.8%, and 4.5% improvement in adherence to process standards; likewise, organisational influence, delivery system design and clinical information systems were related to control of HbA1c, blood pressure, and total cholesterol. Conclusion The state of development of health centre systems is reflected in quality of care outcome measures for patients. The health centre systems assessment tool should be useful in assessing and guiding development of systems for improvement of diabetes care in similar settings in Australia and internationally.